2018
DOI: 10.1039/c7nj03424e
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Bi2S3/ZnO heterostructures: an excellent photocatalyst for visible-light-driven hydrogen generation and photoelectrochemical properties

Abstract: Bi2S3/ZnO heterostructures were synthesized, showing a high catalytic effect in photocatalytic hydrogen generation and organic dye degradation under visible light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 72 publications
4
50
0
Order By: Relevance
“…This core-shell interconnected assembled structure could also transport photo-induced electrons and holes to the binding sites; thus, the efficient oxidation of water occurred in the presence of lactic acid as a sacrificial agent, which is also consistent with previously reported literatures 40 42 . In addition, the core-shell heterostructure may facilitate remarkable electron transfer compared with the pristine one, which can efficiently improve hydrogen production 43 . As it already discussed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This core-shell interconnected assembled structure could also transport photo-induced electrons and holes to the binding sites; thus, the efficient oxidation of water occurred in the presence of lactic acid as a sacrificial agent, which is also consistent with previously reported literatures 40 42 . In addition, the core-shell heterostructure may facilitate remarkable electron transfer compared with the pristine one, which can efficiently improve hydrogen production 43 . As it already discussed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, ZnO has a critical drawback as its photocurrent production is noticeably limited owing to its relatively large band gap energy leading to restriction in the visible light absorption. With the passage of time, great efforts were strategised including organic dyes doping [3], heterostructure nanocomposite synthesis [4,5], organic dyes [6] and quantum dots sensitising [7] to overcome these disadvantages. Among them, the synthesis of inorganic-based heterostructure nanorods can be a promising strategy to overcome the ZnO drawback due to the high surface area of the produced composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the formation of a p–n junction between ZnO and other semiconductors is an interesting strategy to improve the ZnO stability and its photocatalytic activity, being known that the environmental factors such as solution pH, dissolved oxygen level, particle morphology and UV irradiation can have a significant effect on the ZnO stability during catalysis process 38 . Accordingly, recent papers focused on the visible-light photocatalytic activity of various p-n heterojunctions based on ZnO such as ZnO/CuO 39 , 40 , Bi 2 S 3 /ZnO 41 , ZnO/ZnBi 2 O 4 42 or ZnO/CuBi 2 O 4 43 shown that such compounds are featured by a good stability maintaining their photocatalytic ability. Moreover, some reports regarding the photocatalytic activity of ZnO deposited by radio frequency (RF) magnetron sputtering put in evidence that the obtained ZnO nanostructured layers are stable even under UV irradiation and can be used as reusable photo-catalysts in aqueous reactions under a wide range of pH medium for photocatalytic applications 44 , 45 .…”
Section: Introductionmentioning
confidence: 99%